Satisfacción Y Motivación De La Gastronomía Regional En Escárcega, Campeche - Paula Viveros Moreno; Ludwin Jaime Estrada Ramírez; Ninfa Hernández Alegría (European Scientific Journal, ESJ, 2018)
Gastronomy is part of the cultural, social, environmental and economic history of villages and their inhabitants. It is considered one of the economically active activities in the development of each locality, reinforcing tradition in rural areas as part of the same culture and tradition of the people. Therefore, this research has as a general objective to analyze the satisfaction and motivation of people who taste traditional cuisine in the municipality of Escarcega, Campeche, Mexico. As well as tastes and preferences regarding the main dishes that are offered. For the achievement of the objective of this basic research, of descriptive type, a questionnaire was used randomly applied to 1,280 people over 18 years old in the 5 main restaurants of the city, validated by the Cronbach alpha coefficient showing a value of 7, indicating that this instrument has an acceptable degree of reliability, the results were plotted in the Excel 2010 program. As a result, among the dishes that most motivate to consume in the municipality of Escárcega are Pan de cazón, shrimps empanadas, shrimps al coco and the traditional panuchos campechanos, there are a number of people who prefer the consumption of traditional foods in fondas, regional food shops, mainly because of their price that is usually cheaper than a formal dish, but above all, because of the tradition of these foods that have been consumed by generations and that are a fundamental part of preserving their gastronomic traditions.